Study on damage evaluation of bimetal with the lead-free copper alloy (Life evaluation in bending fatigue test with AE method) - TAKUMA, Masanori; SATO, Tomohiro; SAITOH, Ken-ichi; TAKAHASHI, Yoshimasa; HIRAI, Yoshimasa (Kikai Gakkai ronbunshū = Transactions of the Japan Society of Mechanical Engineers, 2022)
Lead bronze had been widely used as the bearing materials. However, the utilization of that material is limited, because the lead and the lead compound are noxious to the human body. Therefore, though the lead free bronze (LFB) alloys using the rare metals are developed, the problem on resources has been pointed out. On the other hand, the powder of LFB including the sulfide (Cu5FeS4) of Cu-Fe-S series was developed, and it was reported that the materials sintered the powder show the higher sliding characteristics than those of lead bronze. Therefore, the bimetal materials sintered after spraying that powder on the substrates have achieved high functionality. However, it is desired to establish the method for quantitatively evaluating the progress of the breakage conditions and for acquiring the design information on the realization of the requested mechanical properties. By comparing the breakage types occurred in the tensile test with the characteristics of the AE events emitted by those types, the parameters for evaluating those types were proposed and those effectiveness were reported in the previous study. On the other hand, the establishment of the life judgment method is desired as the main causes of many breakage accidents are fatigue phenomenon. However, the accident analyses are difficult because the traces of the breakage are not clear as for the fatigue breakage of the sintered materials. In this study, the Ib-value derived from the amplitude distribution of the AE events detected in the fatigue test was applied for the life judgement, and that effectiveness was examined.